Coplanar UHF RFID tag antennna with u-shaped inductively coupled feed for metalic applications - Al Khanjar, Karrar Naji Salman (2016)
RFID stands for Radio Frequency Identifcation. The major purpose that RFID system is built for is to transfer data on a transponder (tag) that can be regained with a transceiver by means of a wireless connection. The contactless Identifcation (ID) system depends on data transmission by radio frequency electromagnetic(EM) signals, and accordingly, the whole functionality is weather independent and non-line-of-sight. These features for ID system copes the optical barcodes limitations, which are weather dependent, line-of-sight, and manual operation requirement.Most of RFID tags consisted of integrated circuit (IC) or a Chip and an antenna. The IC executes all of the data processing and is energized by extracting the power from the interrogation signal transferred by the RFID reader. The tag antenna controls the amount of power transmitted from the reader to the tag and the re ect signal from the tag to the reader. Nevertheless there are no restrictions on the physical parameters of the readers antenna, such as being small or planarin size, these restrictions do stratify on the tags antenna. In a matter of fact, the tag miniaturizing in size is limited by the tag antenna size.This thesis reports on the design, fabrication, and measurement of Ultra High Frequency (UHF) RFID tag antennas (860 to 960 MHz), which can be used in metallic applications. The introduced tag antennas are designed and fabricated to accomplish low tagging costs, good performance, as well as tagging metallic objects with small size tags. First, high gain compact coplanar RFID tag antenna was designed and tested. In this design, a coplanar slim antenna is proposed and designed for metallic objects UHF RFID (860-960)MHz as First stage. The antenna structure etched on FR4 epoxy substrate. The slim antenna has been presented with proximity coupled feeding, two symmetrical coplanar ground layer, and transmission line fed by Ushaped inductively coupled feed. Furthermore, U-shaped inductive feeder consists of two opposing symmetrical U-shaped structures to feed the top radiator for antenna.The antenna size is 97.5x50x1.5 mm3 at 915 MHz. The peak gain and efciency for the antenna reached to 5 dBi and 62% at 915 MHz respectively. The antenna bandwidth is 24.875 MHz (900.125-925) MHz (power reection coefcient lower than -3 dB). The measurement result shows very good impedance matching due to the exibility given by the U-shaped inductive feeder; moreover there is a very good agreement with simulations results. The design shows very high gain and good efciency. This antenna introduced to fll up the need for tagging for long range and mounted for metallic objects such as oil barrels tagging in petrol refneries and gas cylinders.The thesis presented a compact coplanar tag electrically small antenna (ESA)as Final stage. The antenna structure etched on polytetra uorethylene (PTFE)as an upper layer substrate, whereas the bottom layer is FR4 epoxy substrate.This coplanar tag antenna gives us ultimate size reduction as well as better ef-ciency. The presented tag antenna designed with a proximity-coupled feed through,two symmetrical via-load coplanar grounds fed by U-shaped inductively coupled feed through embedded transmission line. This confguration led to antenna size to be 31.x19.5 x3.06 mm3 at 915 MHz, while the total gain and efciency for the antenna are 0.12 dBi and 24% respectively. The vias-coplanar load gives and the U-Shaped inductive coupled feed the antenna exible tuning for antenna impedance.The antenna realized gain bandwidth at half power bandwidth is 14.5 MHz (908- 922.5)MHz at 915 MHz. The impedance of the suggested antennas were simulated then measured to validate the design. At the same time, a fgure of merit was applied for this proposed tag antenna and the results were exposed.This antenna measurement shows very good agreement with the simulation part.The presented RFID Tag antennas are low ost,compact, and with good efciency and good gain that make it ft for tagging metallic applications. Finally, Figure of Merit was applied for Final stage of compact electrically small antenna (ESA) and comparison was presented to provide good validation for the proposed design. In this work, the proposed tag antenna was assessed throughout the study of the ESA performance. The tag antenna assessed with new Figure of Merit, namely, Normalized Bandwidth Gain product (NBG) and Normalized bandwidth Efciency product (NBE). The presented comparison was carried out by (NBG) and (NBE).The results were calculated for both NBG and NBE where they are found to be 0.57 and 0.05 respectively.